FORMULASI ZAKATNOMICS PERSPEKTIF MAQASID SYARIAH - Zaini Miftah; Mustaqim Makki (KASBANA, 2024)
Zakatnomics combines zakat and economic principles in the context of Islamic economics. In the Indonesian context, the level of compliance to pay zakat is still low, accompanied by a lack of public trust in zakat management institutions. Zakatnomics has the potential to make a significant contribution to poverty alleviation, community welfare improvement, and inclusive and sustainable economic development. However, challenges related to public awareness, trust in zakat institutions, and human resource capacity must be overcome. Efforts to educate, socialize, and improve governance and accountability of zakat management institutions and active government involvement are needed to support the optimization of zakatnomics. By overcoming these challenges, zakatnomics can be a solution to sustainable inclusive economic development, integrating spiritual values with economic development, and creating holistic welfare for all people. Hopefully, research that combines the perspectives of zakatnomics and maqasid sharia can provide a more comprehensive understanding of the role of zakat in community economic empowerment and create a positive impact in achieving the goals of Islamic law.